Lateralized versus nonlateralized reverse total shoulder arthroplasty. (August 2021) - Bedeir, Yehia H; Grawe, Brian M; Eldakhakhny, Magdy M; Waly, Ahmed H
Throughout the history of reverse total shoulder arthroplasty, the extent of lateral offset has changed considerably from "too lateral" to "too medial" and has been lately swinging back towards a point somewhere in between. Nonlateralized designs minimize shear forces on the glenoid and decrease force required by the deltoid. Glenoid lateralization decreases impingement and scapular notching and improves range of motion. Humeral lateralization achieves a more anatomic position of the tuberosities while maintaining a nonlateralized center of rotation. Several factors play a role in choosing the extent of lateral offset and method of lateralization.